2020
DOI: 10.3390/ijerph17093265
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Overtime Work on Subjective Social Status and Social Inclusion in the Chinese Context

Abstract: Although researchers have argued that long work hours have been shown to threaten individual health, lead to work-family conflict, and reduce job performance, the effect of overtime work on social-related outcomes has received little attention. Based on the framework of relative deprivation, we attempt to address this important issue by exploring whether, why, and when individuals’ overtime work influences their social attitudes. By using the data of 400 Chinese employees from the China Labor-Force Dynamics Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Examining the effects of overtime work on subjective social status and sense of social inclusion in the Chinese context, findings suggest that workers who had long work hours (more than 40 h/week) are more likely to underestimate their social class perception and feel less social inclusion. Secondly, many findings have indicated that the overtime work in developing countries, such as the United States and Japan is more widespread, and employees suffer from more time-related stress, which leads to more serious psychological and sociological implications (24).…”
Section: Discussionmentioning
confidence: 99%
“…Examining the effects of overtime work on subjective social status and sense of social inclusion in the Chinese context, findings suggest that workers who had long work hours (more than 40 h/week) are more likely to underestimate their social class perception and feel less social inclusion. Secondly, many findings have indicated that the overtime work in developing countries, such as the United States and Japan is more widespread, and employees suffer from more time-related stress, which leads to more serious psychological and sociological implications (24).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive employment and unemployment also have a relationship with status assessments and socio-psychological attitudes. For example, Yashuo Chen, Pengbo Li, Chunjiang Yang found a negative relationship between overtime work and subjective social status, and clarify that this relationship was stronger with a low level of fairness than with a high level of fairness [15]. In a study of the SSS of temporarily unemployed people, Neubert Marie, Suessenbach Philipp, Rief Winfried found that unemployment is associated with lower social status and worsening mental health.…”
Section: Itse-2020mentioning
confidence: 98%
“…Subjective social status (hereinafter referred to as SSS) refers to a person's perception of their position or rank in relation to others, and for young people, status is usually defined in the context of society or school [2]. Theoretical analysis of studies of subjective social status shows that it is most often considered in such aspects as the relationship of SSS with physical and mental health [2][3][4][5][6], the influence of family economic wealth and well-being on the formation of SSS [1,[7][8][9][10], the level of education and training [8,[11][12][13][14], professional and labor activity, employment or unemployment [5,13,[15][16], age [3,5,17,18], national, ethnic [18][19][20], racial [20,21], class [1,22] and gender [3,16,20], valuesemantic sphere [23][24][25] and motivational sphere [26].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above reasons, the educational background of front-line service staff is very different. Therefore, the studies on employee work attitude and behavior in the Chinese service context take employee's income and education as control variables, such as Chen et al [67].…”
Section: Aggregated Emotional Labormentioning
confidence: 99%